Training hotel staff in early emergency management to enhance tourist comfort at Ubud Raya Resort area - Ani, Luh Seri; Hendrayana, Made Agus; Gandari, Ni Komang Matalia; Laksmi, Ida Ayu Agung; Agastiya, I Made Cahyadi; Vittala, Govinda; Juniartha, I Gusti Ngurah; Dwija, Ida Bagus Nyoman Putra (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Tourists who stay at the hotel have a risk of illness and/or experiencing emergency problems that interfere with the sense of security and comfort for tourists. One factor for successful emergency management is first aid proficiency. However, the knowledge and skills of hotel staff are relatively lacking in handling emergency problems for tourists.Â  Based on this, this service was held to train the skills of hotel staff in handling emergencies for tourists. Service activities are carried out by presentation methods and practice on basic life support. The target of this activity is the hotel staff of Ubud Raya Resort. Dedication materials were given in 5 meetings. The training material has been adjusted to travel medicine subjects and based on the results of previous research by the implementation team. The implementation of this service went smoothly and as planned. Based on the results of the pretest and posttest, an increase in the knowledge and skills of participants was obtained. Based on interviews, it was found that service participants received positive benefits from the service carried out. Thus, concluded that this service was successfully carried out despite the limitations in its implementation. This community service advice re-conducting basic life support training for hotel staff so that the knowledge and skills received are beneficial in the long term.